1983
DOI: 10.1016/0002-9416(83)90320-2
|View full text |Cite
|
Sign up to set email alerts
|

An examination of dental crowding and its relationship to tooth size and arch dimension

Abstract: This investigation was undertaken to examine the extent to which tooth size and jaw size each contribute to dental crowding. Two groups of dental casts were selected on the basis of dental crowding. One group, consisting of 50 pairs of dental casts (18 males and 32 females), exhibited gross dental crowding. A second group, consisting of 54 pairs of dental casts (24 males and 30 females), exhibited little or no crowding. Means and standard deviations of the following parameters were used to compare the two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0
31

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(182 citation statements)
references
References 7 publications
7
125
0
31
Order By: Relevance
“…However, other authors have stated that the correlation of crowding and tooth size, or the MD/FL ratio, is weak, and that the correlation between crowding and dental arch size is more significant. [10][11][12][13][14][15] Other factors, such as aging, 16,17 tooth size differences between males and females, 18,19 malocclusion, 20 and race, 21,22 have also been studied.…”
mentioning
confidence: 99%
“…However, other authors have stated that the correlation of crowding and tooth size, or the MD/FL ratio, is weak, and that the correlation between crowding and dental arch size is more significant. [10][11][12][13][14][15] Other factors, such as aging, 16,17 tooth size differences between males and females, 18,19 malocclusion, 20 and race, 21,22 have also been studied.…”
mentioning
confidence: 99%
“…En el grupo con desnutrición crónica el perímetro de arco superior en dentición mixta (PAS) fue mayor en los varones que en las mujeres. Este hallazgo coincide con lo encontrado en los estudios de Moyers (9), Moorrees et al (7) y Howe et al (17 ) quienes refieren que los niños presentan un mayor perímetro de arco que las niñas. Alfano (18) realizó estudios en cerdos, los cuales demuestran que la desnutrición ocasiona una disminución en el crecimiento y desarrollo mandibular.…”
Section: Resultados Y Discusiónunclassified
“…Las diferencias entre las medidas del ancho intermolar superior y ancho intermolar inferior son mayores en niños con oclusión aceptable que en aquellos con maloclusión Clase II división 1 (5). Howe et al (6) encontraron que el ancho intermolar en los casos con apiñamiento fue 6mm menor que en los casos sin apiñamiento.…”
Section: Introductionunclassified
“…Furthermore, how genes translate their codes into crown sizes are not yet fully understood. 9 In the present study, the Chennai population has been loosely defined by more of a social consideration (historical and demographic factors) rather than a biological one as described by Macko et al 10 Since, patients with malocclusions are shown to have no differences in tooth size compared with those with no malocclusions, 5,11 it was therefore accepted that the models of Chennai patients presenting for orthodontic treatment would be a suitable comparison group. A majority of odontometric studies have also found average mesiodistal widths of individual male teeth to be larger than those of female teeth of permanent dentition in any ethnic group.…”
Section: Representativeness Of the Samplementioning
confidence: 98%